Associations of the Need for Surgery in Emergency Department Patients with Small Bowel Obstructions - Daniel J. Berman; Alexander W. Mahler; Ryan C. Burke; Andrew E. Bennett; Nathan I. Shapiro; Leslie A. Bilello (Western Journal of Emergency Medicine)
Objectives: Management strategies for small bowel obstruction (SBO) vary from conservative approaches to surgical intervention. A known complication of surgery is the subsequent adhesions that can cause recurrent SBOs, longer hospital stays, and higher treatment costs. Our primary outcome was to identify independent risk factors that are associated with the decision for surgical intervention, and our secondary outcome was to describe characteristics of visits associated with complications. Methods: This study was a single-center, retrospective chart review from a large, urban university hospital. We included adult patients admitted to the emergency department (ED) with the International Classification of Diseases, 10th Rev, codes for small bowel obstruction from June 1, 2017– May 30, 2019. Eligible covariates were demographics, radiological findings, clinical presentation, past medical history, and results of radiologic testing. We identified univariate associations of outcome and then performed a multivariate logistic regression to identify independent associations of each outcome. Finally, a backwards selection was used to determine the final model. We calculated odds ratios (OR) and 95% confidence intervals (CI) along with the area under the curve (AUC), as appropriate. Results: A total of 530 patients met the study criteria; 148 (27.9%) underwent surgery of whom 35 (6.6%) had complications. We identified seven independent associations for the decision of surgery: abdominal distension (OR 0.27, 95% CI 0.10–0.62); gastrografin (OR 0.41, 95% CI 0.20–0.81); previous SBO (OR 0.42, 95% CI 0.26–0.66); higher Charlson Comorbidity Index score (OR 0.87, 95% CI 0.80–0.95); nasogastric decompression (OR 2.04, 95% CI 1.25–3.39), initial systolic blood pressure <100 mm Hg (OR 2.65, 95% CI 1.05–6.53); free fluid or volvulus/closed-loop obstruction on computed tomography (OR 7.95, 95% CI 4.25–15.39), with the AUC for the predictive model equaling 0.73. Conclusion: We identified seven independent associations present in the ED associated with the decision for surgery. These associations are a step toward building better prediction models and improving decision-making in the ED, allowing for a more adequate treatment plan.